Optimisation in healthcare operations - Leung, Kam San. (2010)
The healthcare industry has expanded rapidly over the past decade, and this trend is projected to continue, particularly in Singapore, where the government invests heavily into the bioscience industry and an aging population is developing. This expansion will cause operational problems to become more complex than ever. As such, it is necessary to look for optimisation methods that could streamline these processes to avoid a fall in efficiency. The objectives of this report are to identify some of the key problems in healthcare operations that can be improved by optimisation techniques, and to develop a tool for optimising operating room schedules.